Age-Related Decline in Verbal Learning Is Moderated by Demographic Factors, Working Memory Capacity, and Presence of Amnestic Mild Cognitive Impairment. (22nd August 2014) - Constantinidou, Fofi; Zaganas, Ioannis; Papastefanakis, Emmanouil; Kasselimis, Dimitrios; Nidos, Andreas; Simos, Panagiotis G
Abstract Age-related memory changes are highly varied and heterogeneous. The study examined the rate of decline in verbal episodic memory as a function of education level, auditory attention span and verbal working memory capacity, and diagnosis of amnestic mild cognitive impairment (a-MCI). Data were available on a community sample of 653 adults aged 17–86 years and 70 patients with a-MCI recruited from eight broad geographic areas in Greece and Cyprus. Measures of auditory attention span and working memory capacity (digits forward and backward) and verbal episodic memory (Auditory Verbal Learning Test [AVLT]) were used. Moderated mediation regressions on data from the community sample did not reveal significant effects of education level on the rate of age-related decline in AVLT indices. The presence of a-MCI was a significant moderator of the direct effect of Age on both immediate and delayed episodic memory indices. The rate of age-related decline in verbal episodic memory is normally mediated by working memory capacity. Moreover, in persons who display poor episodic memory capacity (a-MCI group), age-related memory decline is expected to advance more rapidly for those who also display relatively poor verbal working memory capacity. (JINS, 2014, 20, 1–14)